Solar car drive controller and electrical system design - Chong Kian Keong
Objectives of this project is study and identify several of drive controller and electrical system of solar car, apply theoretical analysis method to identify critical factors in this prototype solar car drive controller and electrical system design and propose improvements that aim for higher efficiency drive controller and electrical system design.